The Sovereignty of Cyberspace - Omar, Omar Mahmoud; Juwaihan , Ma'en (International Journal of Psychosocial Rehabilitation, 2020)
The creation of a virtual world parallel to the material world created a kind of competition for sovereignty, which promoted the idea of a transition to coexistence in these sovereign centers, away from chaos and violence. Recognition of this diversity of sovereignty would lead to the existence of competing forces but in a peaceful and homogeneous manner. The international nature of digital conflicts is certainly a source of difficulty in defining applicable law and jurisdiction. cyberspace has made national boundaries transparent, because inter-network overlaps have made the boundaries intangible. So, it is not surprising that the state loses its legitimacy when it comes to regulatory matters. The contradiction between the geographical and territorial boundaries of national laws and the universality of the Internet led to the loss of the state part of its sovereignty in the area of cyberspace. Limits are not a fixed and unchanging chapter, but they are evolving in place and time and are losing their importance in many areas. Globalization and the existence of a networked world have contributed to building areas where it is difficult to set boundaries accurately.